Altered serum creatine kinase level and cardiac function in ischemia-reperfusion injury during percutaneous coronary intervention - Luo, Yi (International Scientific Literature, Inc., 2011)
BACKGROUND: Myocardial ischemia-reperfusion injury (MIRI) resulting from primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) is considered harmful to the patient, but its clinical significance remains unclear. This study explored the relationship of cardiac function examined by echocardiography and serum creatine kinase (CK) and CK-MB levels with MIRI in a cohort of Chinese AMI patients. MATERIAL/METHODS: We retrospectively analysed the clinical and angiographic data in 228 AMI patients in whom the infarct-related artery (IRA) was successfully recanalized by primary PCI. Cardiac function was evaluated by use of echocardiography before discharge from hospital. RESULTS: The in-hospital mortality rate in the MIRI group was 13.4% (16/119), which was significantly higher than the 4.6% (5/109) mortality rate in the non-MIRI group (P=0.021). The median of peak serum CK level was remarkably lower in the suppression-type MIRI group than in the non-MIRI group. There were no significant differences in the peak serum CK or CK-MB levels between the irritation-type MIRI group and the non-MIRI group. The peak CK and CK-MB levels were significantly higher in the no-reflow-type MIRI group than in the non-MIRI group. Left ventricular ejection fraction in the no-reflow-type MIRI group was significantly lower than in the non-MIRI group; left ventricular end-diastolic volume was significantly higher than in the irritation-type MIRI subgroup; and left ventricular end-systolic volume was greater than that in non-MIRI group and suppression-type MIRI group. CONCLUSIONS: MIRI (especially the no-reflow type) may lead to acute hemodynamic disorders and increase the mortality rate. However, suppression- and irritation-type MIRI may imply the existence of surviving myocardium.